Deciphering the Fenton-reaction-aid lignocellulose degradation pattern by Phanerochaete chrysosporium with ferroferric oxide nanomaterials: Enzyme secretion, straw humification and structural alteration. (March 2019) - Huang, Danlian; Li, Tao; Xu, Piao; Zeng, Guangming; Chen, Ming; Lai, Cui; Cheng, Min; Guo, Xueying; Chen, Sha; Li, Zhihao
Graphical abstract: Highlights: A novel biotechnology combined Fe3 O4 NMs and fungal treatment was proposed. Possible mechanism of enhanced Fenton process was discussed. Interaction between Fe3 O4 NMs and microorganisms was illustrated. Decrystallization of lignocellulose by fungal treatment was observed. Abstract: Nowadays, Nano-biotechnology is emerging to be one of the most promising tools in environmental remediation. In this study, the degradation efficiency of lignocellulose by white-rot fungi was improved by addition of Fe3 O4 nanomaterials (NMs) in solid-state fermentation. The highly-ordered cellulose crystalline was demonstrated to be broken down through infrared spectroscopy (FT-IR) and crystallinity index analysis. The decay of fluorescence intensity presented a lower degree of aromatic polycondensation and less conjugated chromophores in lignocellulose. Mechanistic analysis showed that NMs participated in the Fenton reaction and affected lignocellulose biodegradation process by regulating enzyme secretion. Specifically, the time variation curves of hydroxyl radicals and Fe 2+ were discussed to illustrate the degradation pattern. The NMs remained stable after the fermentation and were possible to be recycled for the next cycle. All the results support that the synergism of Fe3 O4 NMs and white-rot fungi would be a promising research direction in lignocellulose treatment.